Characterization of Protein Methyltransferases Rkm1, Rkm4, Efm4, Efm7, Set5 and Hmt1 Reveals Extensive Post-Translational Modification. Issue 1 (5th January 2018) - Winter, Daniel L.; Hart-Smith, Gene; Wilkins, Marc R.
Abstract: Protein methylation is one of the major post-translational modifications (PTMs) in the cell. In Saccharomyces cerevisiae, over 20 protein methyltransferases (MTases) and their respective substrates have been identified. However, the way in which these MTases are modified and potentially subject to regulation remains poorly understood. Here, we investigated six overexpressed S. cerevisiae protein MTases (Rkm1, Rkm4, Efm4, Efm7, Set5 and Hmt1) to identify PTMs of potential functional relevance. We identified 48 PTM sites across the six MTases, including phosphorylation, acetylation and methylation. Forty-two sites are novel. We contextualized the PTM sites in structural models of the MTases and revealed that many fell in catalytic pockets or enzyme–substrate interfaces. These may regulate MTase activity. Finally, we compared PTMs on Hmt1 with those on its human homologs PRMT1, PRMT3, CARM1, PRMT6 and PRMT8. This revealed that several PTMs are conserved from yeast to human, whereas others are only found in Hmt1. The mass spectrometry proteomics data have been deposited to the ProteomeXchange Consortium via the PRIDE partner repository with the dataset identifier PXD006767. Graphical abstract: Highlights: Protein methylation affects key processes, but its regulation is poorly understood. Six protein MTases are characterized in-depth by MS. Protein MTases are highly post-translationally modified. Structural contextualization indicates that MTases may be subject to regulation. Most comprehensive characterization of PTMs carried by MTases to date.